1997
DOI: 10.1017/s0033822200018932
|View full text |Cite
|
Sign up to set email alerts
|

Apparent 14C Ages of Marine Mollusk Shells from a Greek Island: Calculation of the Marine Reservoir Effect in the Aegean Sea

Abstract: ABSTRACT. The excavation of the Cyclope cave, situated on the deserted island of Youra in the Northern Sporades (39°22'N, 24°10'E), revealed material of marine and terrestrial origin in undisturbed layers, suitable for radiocarbon dating.In some cases, material from different reservoirs was found together in the same archaeological layer. This research had two aims. The first was the dating of charcoal-seashell pairs in order to determine the marine reservoir effect in this region, based on samples with ages s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…As is the case in other regions as well, it is very difficult to trace the ephemeral remains of highly mobile groups of people, except in caves where they have been protected from both erosion and alluvial or colluvial coverage. That Mesolithic populations indeed used the terrestrial and marine resources in the region of Thessaly is demonstrated by the two caves situated in its far west (Theopetra: compare Kyparissi-Apostolika 2000a;2000b;Facorellis et al 2001) and far east (Cyclops Cave on the island of Youra: compare Sampson et al 2003;Facorellis et al 1998). …”
Section: The End Of the Mesolithic And Beginning Of The Neolithic In mentioning
confidence: 98%
“…As is the case in other regions as well, it is very difficult to trace the ephemeral remains of highly mobile groups of people, except in caves where they have been protected from both erosion and alluvial or colluvial coverage. That Mesolithic populations indeed used the terrestrial and marine resources in the region of Thessaly is demonstrated by the two caves situated in its far west (Theopetra: compare Kyparissi-Apostolika 2000a;2000b;Facorellis et al 2001) and far east (Cyclops Cave on the island of Youra: compare Sampson et al 2003;Facorellis et al 1998). …”
Section: The End Of the Mesolithic And Beginning Of The Neolithic In mentioning
confidence: 98%
“…Indeed, Black 14 C dates from millennia prior to the ending of Black surface freshness are roughly 1000 14 C years older than dates indicated by tephrachronology, varve counting, and paleogeomagnetic tests (Arthur and Dean 1998: Section 3). Additionally, a study found that the regional marine reservoir effect near an island in the Aegean, where Black water would have flowed, was roughly zero, or negative, at about the time when the Black freshwater started to be emptied and then increased to about 150 14 C years during the next millennium or so (the study drew no conclusions for after that time) (Facorellis et al 1998). …”
Section: Waters Agingmentioning
confidence: 98%
“…that is known to have been characterized by reduced deep water ventilation [Rohling, 1994;Kallel et al, 1997;Mercone et al, 2000;Casford et al, 2003]. A single shell determination of DR during this period of sapropel deposition gives a DR value of 149 ± 30 years [Facorellis et al, 1998]. Before 9000 years B.P., circulation in the Aegean appears to have generally been similar to the modern since $18,000 years B.P.…”
Section: Marine Reservoir Effectmentioning
confidence: 99%
“…Radiocarbon convention ages were calibrated using marine mode of programme Calib5.1 [Stuiver and Reimer, 1993;Stuiver et al, 1998]. Cores LC-21, LC-31, SL-31, SLA-9, C-40, and SK-1 datings include a local DR correction of 149 ± 39 years [Facorellis et al, 1998] in the sapropel and a DR of 58 ± 85 years [Reimer and McCormac, 2002] outside of the sapropel; see text for further discussion.…”
mentioning
confidence: 99%